Assessment of 3D Printings Produced in Fused Deposition Modeling Printer Using Polylactic Acid/TiO2/Hydroxyapatite Composite Filaments - Olam, Mikail; Tosun, Nihat (Springer, 2022)
Polymer composite filaments, which consist of polylactic acid (PLA), titanium dioxide (TiO2), synthetic hydroxyapatite (HA) and natural hydroxyapatite (NHA), have been produced via an extruder for using in biomedical applications. Then, 3D printings were produced in a fused deposition modeling (FDM) printer by using these composite filaments. A number of experiments and measurements were made on 3D printed PLA/HA/NHA/TiO2 composite samples. According to the stress-strain analysis of 3D printing samples of PLA/HA/NHA/TiO2 composites, the highest ultimate tensile strength, elastic modulus and elongation at break were 62, 1887 MPa, and 1.76 mm, respectively. According to SEM analysis, HA in PLA contributed to the spread of raster lines, and TiO2 contributed to the smoothness of the raster lines. According to the dimensional accuracy analysis of the composites, the least deviation value was obtained in the samples 3D printed with 95%PLA/2.5%HA/2.5%TiO2 filament at 205 degrees C extruder temperature. The lowest average roughness value of 95%PLA/4%HA/1%TiO2 composite was 3 mu m in the Z-axis plane. According to the data obtained, the extruder temperature is 220 degrees C, the printing speed is 2880 mm/min, the mixing ratio 95% PLA/4% HA/1% TiO2 can be selected for optimal performance characteristics.
Keywords: dimensional accuracy; HA; mechanical properties; PLA; surface finish; TiO2